Penurunan Konsumsi Daya (VA) Peralatan Listrik Rumah Tangga Dengan Mereduksi Distorsi Harmonisa - ,., Irman (Faculty of Engineering, Universitas Tanjungpura, 2013)
Abstract Energy consumption is the largest electricity to household customers. Most household electrical load is electronic equipment which is non-linear loads. The load harmonic distortion greatest contributor to the power distribution system. Harmonic distortion leads to wastage of electrical energy due to energy components such as power, power factor, voltage and current conditions deviate from ideal. Measurement of Total harmonic current distortion (THDi) on some household electrical appliances producing harmonics is performed to determine THDi of each different load. Based on the measurement data, conducted the analysis for later Single Tuned Filter is designed to reduce the current harmonic distortion of each load and the total load. By comparing THDi, power factor and power consumption (VA) of the load before and after the filter, it was found that the installations of the filter will cause a decrease in THDi to 31.64, increasing the power factor to 0.87, and decreased power consumption (VA) amoundted to 10.14% if the filters are installed on every load and 13.75% if the filters are installed to total load. Keywords Total Harmonic Current Distortion , Single Tuned Filters